2010
DOI: 10.1007/s11187-010-9272-9
|View full text |Cite
|
Sign up to set email alerts
|

Gender, borrowing patterns and self-employment: some evidence for England

Abstract: This paper analyses the impact that financial constraints have on women"s entrepreneurial choice. The empirical analysis is based on the data provided by the Household Survey of Entrepreneurship database that surveys individuals" intentions of becoming self-employed in England, UK. We do find evidence that women are less likely to seek external finance for business start-ups. This suggests that women in the general population perceive stronger financial barriers to business start-up than men, and this may be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 23 publications
3
52
0
12
Order By: Relevance
“…The phenomenon of the "discouraged borrower" (Kon and Storey 2003;Mijid 2014), a creditworthy individual who does not apply for finance for fear of rejection still seems to be evident among women entrepreneurs (Leitch and Hill 2006). Sena, Scott, and Roper (2012) suggest that women perceive stronger financial barriers to entrepreneurship compared to men, which may discourage them from seeking external financing. However, we still do not have sufficient knowledge and insights into why this is the case: why do women -voluntarily -exclude themselves from external funding?…”
Section: Did You Ask For Finance? Of Gender Stereotypes Perceptions mentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon of the "discouraged borrower" (Kon and Storey 2003;Mijid 2014), a creditworthy individual who does not apply for finance for fear of rejection still seems to be evident among women entrepreneurs (Leitch and Hill 2006). Sena, Scott, and Roper (2012) suggest that women perceive stronger financial barriers to entrepreneurship compared to men, which may discourage them from seeking external financing. However, we still do not have sufficient knowledge and insights into why this is the case: why do women -voluntarily -exclude themselves from external funding?…”
Section: Did You Ask For Finance? Of Gender Stereotypes Perceptions mentioning
confidence: 99%
“…Over the past decade, research has continued to focus on the demand side of financing for women entrepreneurs, studying, for example, women's access to finance at the start-up stage (Sena, Scott, and Roper 2012) or women entrepreneurs' access to external finance Shaw, Carter, and Lam 2010). Other studies have investigated supply-side related issues.…”
mentioning
confidence: 99%
“…One important issue is the gender gap in the business start-up, motivation and intention (Humbert and Drew, 2010;Haus et al, 2013). Consequently a part of earlier studies (Sena et al, 2012;Watson et al, 2009) deals with the question of whether such gender gap is caused by women's greater problems with funding. A large number of previous studies (Brush et al, 2004;Fuller-Love et al, 2006;Muravyev et al, 2009), however, have confirmed that women face greater difficulties than men in receiving bank loans.…”
Section: The Gender Perspective In Businessmentioning
confidence: 99%
“…Ils ont démontré l'importance de l'initiative publique pour encourager la création des entreprises (Heger, Fier et Murray, 2005 ;Piper, 2000), le financement de l'innovation (Dahlstrand et Cetindamar, 2000 ;Chang, Shipp et Wang, 2002 ;Piper, 2000 ;Wessner, 2002) et le développement du marché de CR (Aernoudt, 1999 ;Harrison et Mason, 2000b). Une étude récente a révélé que le bénéfice d'un soutien gouvernemental augmente la propension des femmes à recourir au financement externe et à s'auto-employer au travers d'un projet de création (Sena, Scott et Roper, 2010). Cela étant dit, Revue internationale P.M.E., vol.…”
Section: Le Financement Fourni Par Les Pouvoirs Publicsunclassified
“…Finalement, plusieurs auteurs se sont arrêtés à l'étude des caractéristiques de l'entrepreneur. On y comprend que les femmes sont moins enclines à rechercher du financement externe (Sena, Scott et Roper, 2010) et qu'elles ont plus de difficulté à trouver du financement, notamment par capital-risque (Orhan, 2001 ;Kim, 2006 ;Alsos, Isaksen et Ljunggren, 2006). Ces résultats ne doivent cependant pas être liés à l'hypothèse de sexisme financier qui avait été formulée au début des années 2000, mais à des caractéristiques intrinsèques au comportement des femmes et à leurs choix stratégiques (Constantinidis, Cornet et Asandei, 2006).…”
Section: Introductionunclassified